Experimental Investigation of Mechanical Properties on Bacterial Concrete M-Sand (International Journal of Scientific Research in Science and Technology, 2024)
This research shows that using Bacillus Subtilis microorganisms to build a tough framework and put forward a concentrated effort mending concrete as a strategy for break control to improve administration existence in solid structures is successful. The Microbiologically Induced Calcite Precipitation (MICP) method is used in this article. A 24 ml liquid form of Bacillus Subtilis with a cell concentration of 105 cells/ml was used in a 1:1.3: 2.75:0.45 mixing proportion. The compressive and flexural strength of concrete mixes was tested using 150mm x 150mm x 150mm cubes for compressive strength and 150mm x 150mm x 70mm rectangular beams for flexural strength. The specimens used for recovery are purposefully broken. The research shows that there is a significant improvement in the consistency of bacteria-added cement or bacterial concrete as compared to traditional concrete, and that calcium carbonate precipitation is visible after 3-4 weeks in small scale splits.
Keywords: Sand; Msand; Cement; Bacterial Concrete